INCREASED FRONTAL SEROTONERGIC FUNCTION IN PARKINSON’S DISEASE PATIENTS WITH SELF-REPORTED REM SLEEP BEHAVIOR DISORDER - Ijas, Jani (My University, 2025)
Rapid eye movement (REM) sleep behavior disorder (RBD) is a frequent non-motor symptom of Parkinson’s disease (PD) and a potential early marker of synucleinopathy-related neurodegeneration. While striatal dopaminergic dysfunction in PD-RBD has been extensively studied, the role of extrastriatal monoaminegic alterations -particularly serotonergic - remains poorly understood. In this study, 155 PD patients underwent [123I]FP-CIT SPECT imaging to assess striatal and extrastriatal tracer binding, reflecting dopaminergic and serotonergic function, respectively. Probable RBD was identified using a validated single-question screening tool with high sensitivity and specificity. Patients with probable RBD (RBD+, n=44) were compared to those without (RBD−, n=111) using voxel-wise and region-of-interest analyses, controlling for age, sex, disease duration, motor and non-motor symptom severity, and cognitive function. No significant differences were observed in striatal dopamine transporter binding. However, RBD+ patients showed significantly higher extrastriatal binding in the prefrontal cortex (pFWE<0.05), suggesting a role for altered serotonergic neurotransmission in PD-RBD pathophysiology.
Keywords: Parkinson’s disease, RBD, SPECT, serotonin